The Demands of Employers and the English Competency of the Workforce in the Eastern Economic Corridor of Thailand - It-ngam, Suparuthai; Saejew, Budsabong; Kunprayoonsawat, Rapeephan (LEARN Journal: Language Education and Acquisition Research Network, 2023)
The Eastern Economic Corridor (EEC) is a promising project which aims to elevate the living standards of the Thai people. Large numbers of skilled workers with a good command of the English language are urgently needed. The present study aims to examine the English proficiency of Thai employees and explore the expectations of employers in the EEC. The instruments used in the study include an English proficiency test, interviews, and a survey of employees. The findings indicate that employees working with the top management level, (e.g., managers and supervisors) are expected to be more proficient in English than those working at the operational level. Among four modes of communication, the performance of most participants in reception and production were in the same range (A2 – B2). On the other hand, the performance in interaction and mediation fell into the lower range (A1 – B1). New employees are expected to be able to communicate in English at a good level and then learn to use technical English in their fields.